2022
DOI: 10.1210/clinem/dgac635
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Patient With a Suppressed TSH

Abstract: Subclinical hyperthyroidism is a laboratory diagnosis defined by a serum thyroid stimulating hormone (TSH) concentration below the reference range (< 0.4 mU/L in most assays), and a free thyroxine (FT4) and triiodothyronine levels (FT3) in the reference range. Many patients diagnosed with subclinical hyperthyroidism will be clinically euthyroid while others may present with manifestations characteristic of thyroid hormone excess, such as tachycardia, tremor, intolerance to heat, bone density loss, or we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…There is wide agreement in treating persistently TSH levels < 0.1 mU/L in subjects ≥ 65 years [55], since a greater risk of hyperthyroidism-related complications and progression to overt hyperthyroidism have been reported in subjects with TSH levels < 0.1 mU/L compared to those with persistent TSH levels between 0.1 and 0.4 mU/L. There is less evidence supporting the treatment of subclinical hyperthyroidism in subjects with persistent TSH levels between 0.1 and 0.4 mU/L [56]. Some studies have revealed that even mild subclinical hypothyroidism could entail a higher risk of adverse outcomes in older patients, including cardiovascular disease, bone fragility and overall mortality; treatment for mild subclinical hyperthyroidism should also be considered in this population [57].…”
mentioning
confidence: 95%
“…There is wide agreement in treating persistently TSH levels < 0.1 mU/L in subjects ≥ 65 years [55], since a greater risk of hyperthyroidism-related complications and progression to overt hyperthyroidism have been reported in subjects with TSH levels < 0.1 mU/L compared to those with persistent TSH levels between 0.1 and 0.4 mU/L. There is less evidence supporting the treatment of subclinical hyperthyroidism in subjects with persistent TSH levels between 0.1 and 0.4 mU/L [56]. Some studies have revealed that even mild subclinical hypothyroidism could entail a higher risk of adverse outcomes in older patients, including cardiovascular disease, bone fragility and overall mortality; treatment for mild subclinical hyperthyroidism should also be considered in this population [57].…”
mentioning
confidence: 95%